2007
DOI: 10.1537/ase.061203
|View full text |Cite
|
Sign up to set email alerts
|

Early Pleistocene Homo erectus fossils from Konso, southern Ethiopia

Abstract: Homo erectus has been broadly defined to include fossils from Africa, Asia, and possibly Europe, or restricted to a supposedly confined Asian clade. Recently discovered fossils of H. erectus are allowing new insights into aspects of its evolution, such as the timing and mode of the species' emergence in Africa and its relationship to Asian populations. However, the currently available African record predating 1.0 Ma is poor, consisting of the Turkana basin, Olduvai and the more limited South African materials.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 68 publications
5
43
0
Order By: Relevance
“…This association works relatively well for 1.6-1.3 Myr Acheulean assemblages in Konso [106] and, possibly, Olduvai Gorgeas no Homo habilis remains are reported from Middle Bed II (i.e. when handaxes begin to appear in the Olduvai record), and the OH9 erectus calvaria is attributed to Upper Bed II.…”
Section: (E) Human Fossils and Stone Tool Associationssupporting
confidence: 57%
See 1 more Smart Citation
“…This association works relatively well for 1.6-1.3 Myr Acheulean assemblages in Konso [106] and, possibly, Olduvai Gorgeas no Homo habilis remains are reported from Middle Bed II (i.e. when handaxes begin to appear in the Olduvai record), and the OH9 erectus calvaria is attributed to Upper Bed II.…”
Section: (E) Human Fossils and Stone Tool Associationssupporting
confidence: 57%
“…In Sterkfontein Member 5, contextual association between the Early Acheulean and the human remains attributed to H. erectus is unclear [72]. While the early age of H. erectus remains in East Turkana-1.9 Myr for KNM-ER 1813 (but see [106]) and ca 1.63 Myr for KNM-ER 3733 [107]-is often cited to highlight the co-emergence of a new technology alongside a new human species, Koobi Fora is precisely the area where no clear evidence of earliest Acheulean exists.…”
Section: (E) Human Fossils and Stone Tool Associationsmentioning
confidence: 99%
“…However, tooth rotation is a relatively commonly observed dental anomaly both in modern (Jacob et al, 2006;Lukacs et al, 2006) and pre-modern (e.g. Early Pleistocene Homo from Dmanisi (Rightmire et al, 2006) and Konso (Suwa et al, 2007)) hominins as well as other mammals (Natsume et al, 2006), with suggested etiologies including some genetic mechanism and a lack of space for the normal tooth eruption (Baccetti, 1998;Natsume et al, 2006). Therefore this trait is not taxonomically diagnostic and does not necessarily indicate a severe growth abnormality.…”
Section: P 4 Rotationmentioning
confidence: 99%
“…Field research and laboratory analysis thereafter established that the formation spans the time period >1.9 to ∼0.8 Ma (20)(21)(22). Abundant lithic assemblages and vertebrate fossils have been recovered (23)(24)(25), including fossil remains of Australopithecus boisei (∼1.43 Ma) and H. erectus (∼1.45 to ∼1.25 Ma) (19,26,27).…”
mentioning
confidence: 99%